The surgical technique of bilateral sequential lung transplantation - Hayanga, J. W. Awori (Pioneer Bioscience Publishing Company, 2014)
Since the first successful lung transplant performed three decades ago, the technique of lung transplantation has evolved with acceptable short- and long-term outcomes such that it has become the standard for those with end stage pulmonary disease. Herein, we describe our current favored approach and discuss some of the current areas in need of further investigation as they relate to the technical aspects of the operation.